2020
DOI: 10.3390/rel12010027
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Health in Brazil: A Survey Snapshot of Research Groups

Abstract: Articles on “Spirituality and Health” have multiplied considerably in Brazil in the last decade. More recently, however, research groups created specifically to investigate this topic have emerged. This study aims to provide an overview of the field by means of a survey in the Directory of Research Groups in Brazil. Thirty-three groups were initially identified, of which 16 were selected for analysis and placed into two categories: “established” groups and lines of research, and “in-process” groups and lines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this cultural context, studies investigating the relationship between spirituality and health have been gaining increasing attention in recent years. Evidence comes from the increase in research groups in Spirituality and Health in graduate programs, according to a recent survey (Esperandio 2020). Brazil also falls in 13th place in the international ranking of publications in the Scopus database and "5th place in articles on medicine, psychology and nursing that include R/S, in the last five years" (Moreira-Almeida and Lucchetti 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cultural context, studies investigating the relationship between spirituality and health have been gaining increasing attention in recent years. Evidence comes from the increase in research groups in Spirituality and Health in graduate programs, according to a recent survey (Esperandio 2020). Brazil also falls in 13th place in the international ranking of publications in the Scopus database and "5th place in articles on medicine, psychology and nursing that include R/S, in the last five years" (Moreira-Almeida and Lucchetti 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A predominantly positive perspective on the impact of religion and spirituality characterizes Brazilian studies in this field. Therefore, it is urgent to investigate other aspects as well, such as the implications of negative religious/spiritual (R/S) coping and R/S struggles for health outcomes, as already pointed out by Brazilian researchers (Moreira-Almeida and Lucchetti 2016;Esperandio 2020). Such studies can contribute to a better understanding of how the R/S dimension acts or interferes in health/illness processes in different scenarios, for example, in the current context of the COVID-19 pandemic (Pargament and Exline 2022), in mental health (Ellison et al 2013;Plante 2020;Exline et al 2021), and in palliative care (Damen et al 2021) and end-of-life care (Puchalski et al 2016), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Villela et al also found that the pandemic had a crucial impact on HCWs’ work routines, with a high rate of AS [ 28 ]. It is noteworthy that spirituality research in Brazil has great relevance due to its cultural context since spirituality and religion are commonplace within Brazilian culture [ 30 , 31 ]. Indeed, most of the Brazilian population has a religious affiliation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%